1986
DOI: 10.1139/f86-018
|View full text |Cite
|
Sign up to set email alerts
|

Individual Parameter Perturbation and Error Analysis of Fish Bioenergetics Models

Abstract: We quantified the sensitivity of predicted rates of growth and consumption to parameter variation for models of yellow perch (Perca flavescens), largemouth bass (Micropterus salmoides), and alewife (Alosa pseudoharengus). We used statistical analyses of the results of Monte Carlo simulations to rank parameter importance. The order of parameter importance was model specific, although the results emphasized the need for accurate estimation of the realized fraction of maximum consumption rate (P) and allometric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
198
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(204 citation statements)
references
References 13 publications
5
198
1
Order By: Relevance
“…The basics are discussed in Grimm and Railsback 2005, Chapter 9. More extensive discussions of biological applications of sensitivity analysis can be found in Bartell et al 1986 andDreschler 1998. For more general discussions, see Rose 1989, Vose 2000, and Saltelli et al 2004 reason to believe that the basic structure of her model is adequate for her purposes, but remains uncertain about the values that should be assigned to the parameters.…”
Section: ) Dtmentioning
confidence: 99%
“…The basics are discussed in Grimm and Railsback 2005, Chapter 9. More extensive discussions of biological applications of sensitivity analysis can be found in Bartell et al 1986 andDreschler 1998. For more general discussions, see Rose 1989, Vose 2000, and Saltelli et al 2004 reason to believe that the basic structure of her model is adequate for her purposes, but remains uncertain about the values that should be assigned to the parameters.…”
Section: ) Dtmentioning
confidence: 99%
“…Sensitivity analyses have demonstrated that for most species, including perch, consumption and respiration parameters are decisive for the model's output (Kitchell et al 1977;Bartell et al 1986;Horppila and Peltonen 1997). In a recent evaluation of bioenergetic models for yellow perch Perca flavescens, Bajer et al (2003) found strong evidence of deficiencies in estimates of the metabolic rate.…”
mentioning
confidence: 99%
“…In these cases, respiration might be overestimated. Because bioenergetic model outputs are very sensitive to the respiration parameters in many species (Kitchell et al 1977;Bartell et al 1986;Horppila and Peltonen 1997;Madenjian et al 2006), the resulting growth or consumption estimates may be severely flawed. The input parameter set for yellow perch listed in Hanson et al (1997) was derived from Kitchell et al (1977), who in turn based their model on the respiration measurements of Solomon and Brafield (1972) ).…”
mentioning
confidence: 99%
“…The individual perturbation method of sensitivity analysis (Kitchell et al, 1977;Bartell et al, 1986;Cui and Wootton, 1989;Liu, 1998) was used to assess the sensitivity of the output of the bioenergetics models of the variations of the parameters used. Single parameter values were changed by a constant fraction, while the other parameters remained fixed.…”
Section: Sensitivity Analysis Of the Bioenergetics Modelsmentioning
confidence: 99%